2021
DOI: 10.1186/s13256-021-02961-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of cavitary lung disease as a long-term complication of coronavirus disease 2019 in a young previously healthy patient: a case report

Abstract: Background Cavities are frequent manifestations of a wide variety of pathological processes involving the lung. There has been a growing body of evidence of coronavirus disease 2019 leading to a cavitary pulmonary disease. Case presentation A healthy 29-year-old Filipino male presented to the hospital a couple of months after convalescence from coronavirus disease 2019 with severe pleuritic chest pain, fever, chills, and shortness of breath, and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Only two patients were treated using invasive therapies. One patient underwent CT-guided drainage ( 13 ), and another underwent video-assisted thoracic surgery for decortication ( 9 ). Both patients were successfully treated and recovered from the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Only two patients were treated using invasive therapies. One patient underwent CT-guided drainage ( 13 ), and another underwent video-assisted thoracic surgery for decortication ( 9 ). Both patients were successfully treated and recovered from the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing cases of COVID-19 patients with cavitary lung lesions, re-positive or long-term positive nucleic acid tests (Chen et al, 2020a;He et al, 2020;Qiao et al, 2020;Selvaraj and Dapaah-Afriyie, 2020;Lu et al, 2020a;Lu et al, 2020a;Wang et al, 2020b;Aggarwal et al, 2021;Afrazi et al, 2021;Chen et al, 2021;Egoryan et al, 2021;Jafari et al, 2021;Liang et al, 2021;Ozgur and Dogan, 2021;Wu et al, 2021;Zhu et al, 2021;Zoumot et al, 2021;He et al, 2022;Maccio et al, 2022). Lung cavities appear at a long-time interval from initial novel coronavirus infection, generally during the absorption phase of the disease, may have severer symptoms after initial recovery and also an increasing mortality rate (Aggarwal et al, 2021;Chen et al, 2021;Egoryan et al, 2021;He et al, 2022;Zoumot et al, 2021). Maccio et al performed autopsies on 35 COVID-19 patients and found that patients could still show diffuse alveolar damage 2 months after the initial diagnosis of COVID-19 (Maccio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Cavitary or cystic lung lesions in COVID-19 patients may be the result of direct SARS-CoV-2 infection, co-infection with bacterial, fungal or mycobacterial pathogens, secondary to co-existing interstitial lung lesions, cystic bronchiectasis, or barotrauma related to mechanical ventilation, malignancy or metastasis ( Aggarwal et al., 2021 ). COVID-19 patient complicated with pulmonary cavities has a wide age span, including infant, child, adult and elderly patient ( Chen et al., 2021 ; Egoryan et al., 2021 ; Ozgur and Dogan, 2021 ; Zoumot et al., 2021 ; He et al., 2022 ), can appear in both severe and mild COVID-19 ( Selvaraj and Dapaah-Afriyie, 2020 ; Chen et al., 2020a ; Afrazi et al., 2021 ; Aggarwal et al., 2021 ; Chen et al., 2021 ; Jafari et al., 2021 ; Zoumot et al., 2021 ; Kalenchic et al., 2022 ). Some scholars consider lung cavity formation as a late complication during COVID-19 recovery ( Zoumot et al., 2021 ; Egoryan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al further stated that these signs imply a continuing resolution of the lung findings [33]. There are a few case reports and case series that report longterm complications of atelectasis, pleural effusions, occlusion of common femoral arteries, saddle pulmonary embolism, cysts, cavitation with sequelae of superinfection from Aspergillus fumigatus, pneumothorax, and interstitial fibrosis, in addition to the GGOs reported in previous studies [34][35][36][37][38][39][40][41][42][43].…”
Section: Late Ct Scanmentioning
confidence: 94%